Hepatitis A, B, and A/B vaccination series completion among US adults: A claims-based analysis. Issue 11 (2nd November 2018) - Ghaswalla, Parinaz K.; Patterson, Brandon J.; Cheng, Wendy Y.; Duchesneau, Emilie; Macheca, Monica; Duh, Mei Sheng
ABSTRACT: Hepatitis A and B disease burden persists in the US. We assessed hepatitis A and hepatitis B vaccination series completion rates among 350, 240 commercial/Medicare and 12, 599 Medicaid enrollees aged ≥19 years. A vaccination series was considered as completed provided that the minimum interval between doses, as defined by the CDC, and the minimum number of doses were reached. We stratified completion rates by vaccine type (i.e. monovalent or bivalent) at initial vaccination for each cohort. In the commercial/Medicare cohort, the series completion rate was 32.0% for hepatitis A and 39.6% for hepatitis B among those who initiated with a monovalent vaccine, and it was 36.2% for hepatitis A and 48.9% for hepatitis B among those who initiated with a bivalent vaccine. In the Medicaid cohort, the series completion rate was 21.0% for hepatitis A and 24.0% for hepatitis B among those who initiated with a monovalent vaccine, and it was 19.0% for hepatitis A and 24.6% for hepatitis B among those who initiated with a bivalent vaccine. In conclusion, hepatitis A and B vaccination series completion rates were low, and appeared to be lower among Medicaid than among commercial/Medicare enrollees. Commercial/Medicare enrollees who initiated with a bivalent vaccine had higher series completion rates than those who initiated with monovalent vaccines – an observation that was not made among Medicaid enrollees.